PENGARUH STRATEGI PEMBELAJARAN CONTEXTUAL TEACHING LEARNING (CTL) DAN PEMANFAATAN LKPD PORTOFOLIO TUGAS SISWA TERHADAP KEMANDIRIAN BELAJAR SISWA SWASTA BUDISATRYA - Isna Siagian; Toni Nasution (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2024)
The purpose of this study is to determine how the independence of seventh-grade students at Budisatrya Private Junior High Schoolis affected by the use of LKPD student assignment portfolios and Contextual Teaching Learning (CTL) learning methodologies. This kind of research is quantitative, and inferential research is quantitative research. SMP Swasta Budisatrya will host this study. The population consisted of 61 students drawn from two classes, VII-1 and VII-2. The sample consisted of all 61 students. Multiple linear regression analysis was the data analysis method employed in this study. These are the study's findings. Since the sig value is 0.00 <0.05, the study's hypothesis—that contextual teaching and learning have an impact on students' learning independence in class VII at SMP Swasta Budisatrya—is accepted. Given that the sig value of 0.000 <0.05, the hypothesis that there is an impact of the student assignment portfolio LKPD on the learning independence of the SmpSwasta Budisatrya class is accepted in this study. According to the study, LKPD Portfolio and CTL both significantly impact students' learning independence in class VII at SMP Swasta Budisatrya since the significance level of 0.000 <0.05 and the value of f count> f table (33.805> 3.15).